2010
DOI: 10.2174/1874434601004010042
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Students’ Self-Graded Motivation to Complete their Programme of Study

Abstract: The aim of this study was to explore variation in nursing students’ motivation to complete their programme of study, as well as factors relating to low versus high motivation and students’ opinions of what would increase their motivation to complete their programme of study.A study was carried out between April 2006 and December 2007. A total of 872 students registered in a 3-year nursing programme randomly participated in self-rating their motivation score once each semester. Descriptive statistics, statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 30 publications
1
10
0
1
Order By: Relevance
“…In other studies performed with nursing candidates, similar results were found [6,32]. In a study performed in Sweden motivation was found to be higher in the first years of nursing education [26]. The motivation of students includes internal and external factors, and sometimes these factors may interact [7,32].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In other studies performed with nursing candidates, similar results were found [6,32]. In a study performed in Sweden motivation was found to be higher in the first years of nursing education [26]. The motivation of students includes internal and external factors, and sometimes these factors may interact [7,32].…”
Section: Discussionsupporting
confidence: 74%
“…In this context, increasing the education and clinical application motivation of students would be important in the positive development of their self-esteem and professional self-concept [24]. In a number of studies, motivation was found to positively affect academic performance [25][26][27]. Additionally, it has been stressed that motivation increases occupational development and service recipient satisfaction [28,29].…”
Section: Research Articlementioning
confidence: 99%
“…Our study showed that an important intrinsic motivation for students to remain in their programmes was their passionate desire to become nurses, suggesting that the desirable elements of a nursing career outweighed the problems they encountered. This desire can manifest itself at a very young age, and for some students nursing had always been a career goal (Day et al, 2005;Stomberg and Nilsson, 2010). Support from family and friends, and support from tutors and school staff proved to be extrinsic factors which really influenced their decision to pursue nursing.…”
Section: Motivations For Withdrawal and Continuationmentioning
confidence: 99%
“…[ 12 ] Studies have shown that, despite the fact that nursing students start the program with high motivation, their motivation declines throughout the program. [ 2 7 13 14 15 ]…”
Section: Introductionmentioning
confidence: 99%